Separation and characterization of unknown impurities in rutin tablets using trap‐free two‐dimensional liquid chromatography coupled with ion trap/time‐of‐flight mass spectrometry. (5th March 2020) - Wang, Jian; Ren, Xiaojuan; Wen, Chunmei; Xu, Yu; Chen, Yue
Abstract : Rationale: A new high‐performance liquid chromatography method was developed for the determination of impurities in rutin tablets to improve on the method of the official monograph in national drug standards. Five impurities in rutin tablets were characterized using trap‐free two‐dimensional liquid chromatography coupled with ion trap/time‐of‐flight mass spectrometry (2D‐LC/IT‐TOFMS) in both positive and negative ion modes of electrospray ionization. Methods: In the first dimension, the LC column was a Thermo Acclaim 120™ C18 (4.6 mm × 250 mm, 5 μm), and the mobile phase was composed of 0.1 M sodium dihydrogen phosphate aqueous solution (pH adjusted to 4.4 with phosphoric acid) and acetonitrile (80:20, v/v). In the second dimension, the column was a Shimadzu Shim‐pack GISS C18 (50 mm × 2.1 mm, 1.9 μm), and the mobile phase was composed of 10 mM ammonium formate solution and methanol. Results: The structures of five impurities in rutin tablets were deduced based on the MS n data in both positive and negative ion modes, in which two impurities were unknown. Impurity 1, impurity 2 and impurity 3 were proposed as flavonol 3, 7‐di‐ O ‐glycoside, flavonol mono‐ O ‐triglycoside and quercetin 3‐ O ‐glycoside, respectively, and impurity 4 and impurity 5 were proposed as kaempferol 3‐ O ‐rhamnosylglucoside and isorhamnetin 3‐ O ‐rhamnosylglucoside, respectively. Conclusions: The method established in this study was simple and reliable for the routine quality control of rutin tablets. The contradiction between non‐volatile salt mobile phase and mass spectrometry was solved by means of a multiple heart‐cutting 2D‐LC approach and on‐line desalination technology. Five impurities were separated and characterized. These results provide a scientific basis for further improving the national drug standard of rutin tablets.